2023
DOI: 10.1152/ajpheart.00391.2022
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin attenuates arrhythmogenesis in diabetic cardiomyopathy by normalizing intracellular Ca2+ handling in ventricular cardiomyocytes

Abstract: Diabetic cardiomyopathy has been reported to increase the risk of fatal ventricular arrhythmia. The beneficial effects of the selective sodium-glucose co-transporter 2 inhibitor have not been fully examined in the context of anti-arrhythmic therapy, especially its direct cardioprotective effects despite the negligible SGLT2 expression in cardiomyocytes. We aimed to examine the anti-arrhythmic effects of empagliflozin (EMPA) treatment on diabetic cardiomyocytes, with a special focus on Ca2+ handling. We conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The cardiovascular system is complex, and the posttranslational modification of serine and threonine residues in nuclear, cytoplasmic and mitochondrial proteins by O-GlcNAcylation is considered an important regulatory mechanism in the cardiovascular system. Changes in O-GlcNAcylation may lead to many metabolic imbalances and affect cardiovascular function; and this process has an prominent role in heart remodeling [55,120,121], heart failure [22,26,122], diabetic cardiomyopathy [123][124][125], ischemic heart disease [24,42,126], hypertension [127] and arrhythmia [128,129]. Protein O-GlcNAcylation reprograms the cardiac substrate metabolism under chronic stress to advantageously alter adaptation [130].…”
Section: Role Of O-glcnacylation In Cardiovascular Diseases (Cvds)mentioning
confidence: 99%
“…The cardiovascular system is complex, and the posttranslational modification of serine and threonine residues in nuclear, cytoplasmic and mitochondrial proteins by O-GlcNAcylation is considered an important regulatory mechanism in the cardiovascular system. Changes in O-GlcNAcylation may lead to many metabolic imbalances and affect cardiovascular function; and this process has an prominent role in heart remodeling [55,120,121], heart failure [22,26,122], diabetic cardiomyopathy [123][124][125], ischemic heart disease [24,42,126], hypertension [127] and arrhythmia [128,129]. Protein O-GlcNAcylation reprograms the cardiac substrate metabolism under chronic stress to advantageously alter adaptation [130].…”
Section: Role Of O-glcnacylation In Cardiovascular Diseases (Cvds)mentioning
confidence: 99%
“…It is therefore noteworthy that sodium–glucose cotransporter 2 (SGLT2) inhibitors – which are effective in the prevention and treatment of chronic heart failure – can promote nutrient deprivation signalling through AMPK and SIRT1 ( Figure ) 171 . Although SGLT2 is not expressed in cardiomyocytes, SGLT2 inhibition prevents CaMKII activation, spontaneous calcium sparks and impaired calcium transients in the hearts of mice with experimental type 2 diabetes 172 . These effects might be mediated by an indirect action of SGLT2 inhibitors to inhibit the late sodium current, potentially mediated by either interference with CaMKII or by an action to attenuate O‐GlcNAcylation of Na v 1.5, 119,173 since these effects of SGLT2 inhibition were prevented by inhibition of OGA 172 .…”
Section: Potential Modulation Of O‐glcnacylation As a Treatment For H...mentioning
confidence: 99%
“…171 Although SGLT2 is not expressed in cardiomyocytes, SGLT2 inhibition prevents CaMKII activation, spontaneous calcium sparks and impaired calcium transients in the hearts of mice with experimental type 2 diabetes. 172 These effects might be mediated by an indirect action of SGLT2 inhibitors to inhibit the late sodium current, potentially mediated by either interference with CaMKII or by an action to attenuate O-GlcNAcylation of Na v 1.5, 119,173 since these effects of SGLT2 inhibition were prevented by inhibition of OGA. 172 The investigators proposed that the reduction in O-GlcNAcylation was related to an observed reduction of glucose uptake by cardiomyocytes following SGLT2 inhibition, an action that is unrelated to the presence or absence SGLT2 protein 172,174,175 but possibly related to a direct or indirect effect of SGLT2 inhibitors to inhibit GLUT1.…”
Section: Therapeutic Suppression Of Excessive O-glcnacylation In Hear...mentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial effects of SGLT2is on DCM are shown in Table 1 . SGLT2is have multiple beneficial factors that improve DCM [ 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ]. SGLT2is decreased fibrosis, reduced inflammation and improved systolic function.…”
Section: The Effects Of Sglt2is On Causative Pathological Conditions ...mentioning
confidence: 99%